2014
DOI: 10.1007/s00005-014-0323-9
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Approaches to Improve Nerve Regeneration: Potential Implications for Reconstructive Transplantation?

Abstract: Reconstructive transplantation has become a viable option to restore form and function after devastating tissue loss. Functional recovery is a key determinant of overall success and critically depends on the quality and pace of nerve regeneration. Several molecular and cell-based therapies have been postulated and tested in pre-clinical animal models to enhance nerve regeneration. Schwann cells remain the mainstay of research focus providing neurotrophic support and signaling cues for regenerating axons. Alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 173 publications
0
15
0
Order By: Relevance
“…Some studies confirm their differentiation into neuronal cells, both morphologically and functionally (Seo et al 2005). Many researchers see hope in treatment of nerve injuries using ASCs thus, confirming their participation in neuronal regeneration (Mizuno et al 2012; Khalifian et al 2015; Zack-Williams et al 2015). …”
Section: Multilineage Differentiation Potential Of Ascsmentioning
confidence: 89%
“…Some studies confirm their differentiation into neuronal cells, both morphologically and functionally (Seo et al 2005). Many researchers see hope in treatment of nerve injuries using ASCs thus, confirming their participation in neuronal regeneration (Mizuno et al 2012; Khalifian et al 2015; Zack-Williams et al 2015). …”
Section: Multilineage Differentiation Potential Of Ascsmentioning
confidence: 89%
“…Adipose-derived stem cells (ASCs) are ideal pluripotent cells for producing various types of tissues through tissue engineering for clinical application [11]. For instance, autologous ASCs and their clinical efficacy and safety in tissue regeneration have been investigated from breast reconstruction to neural regeneration in the spinal cord [12][13][14]. Autologous ASCs accelerate wound healing in the treatment of chronic ulcers of lower extremities in peripheral artery disease, which is closely associated with DM [15].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies in animal models have demonstrated the ability of MSCs to facilitate peripheral nerve regeneration through differentiation into and interaction with SC [175][176][177][178][179]. Local administration of adipose-derived MSCs in a mouse model of a crush nerve injury demonstrated improved recovery of motor and sensory function [180], and recovery of motor function was also improved by MSC treatment in a rat model of nerve transection [176].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 95%